Oser la performance théâtrale plurilingue à l'école pour une éducation au développement durable - Sandrine Eschenauer (Université de Provence, 2021)
This article focuses on the social dimension of the sustainable development goals set by the OECD (2018). In order to achieve them, it is becoming urgent to (re)give a central place to sensitive or "aesthetic" intelligence at school, i.e. sensory and emotional intelligence. Sensitivity is necessary for the development of empathic literacy. Thus, we define empathy as balanced emotionally and cognitively. It will enable the development of both high-level cognitive skills (abstraction, analysis, critical thinking, etc.) and prosocial skills that are essential to the goals of peace and gap reduction between individuals. Finally, research findings will allow us to attest that in order to build a balanced, equitable society, the practice of artistic disciplines in different languages, and particularly plurilingual theater as a "social and polyaesthetic art", should find a place of choice in French schools, which is not the case today. We will show the effects of such a practice through the field of enaction in education.